Diseño e implementación de una herramienta visual que permita la creación de nuevos componentes SWING utilizando JAVA 2D y 3D. - Calle Loja, Darwin Augusto (2009)
his work with the subject: Design and implementation of a visual tool that allows the creation of new Swing components using Java2D and Java3D has as its main objective to solve the lack of visual tools to improve the graphical appearance of the Swing controls in different applications java performed. The design of the entire application is designed by object-oriented paradigm, so it was necessary diagrams Use Case, Class Diagram, Prototype Screens, diagrams Robustness and Sequence Diagrams for each Use Case, this will he used the UML modeling tool, Enterprice Architect. For the construction of the application was used based on the Java virtual machine to perform the entire thesis project was introduced to the project for carrying out tasks with OS 1.7.0 and Apache-Ant for persistent objects in java XML used. Regarding the coupling of the components generated by the application Evolution Swing JavaBeans technology was used to achieve recognition within the tool NetBeans 5.0 and later. As programming environment NetBeans 6.0, which is available free IDE that helps ease of programming in the Java language was used. Java2D, which contains a very extensive and generation techniques applicable to effects controls Swing API was used to build new custom Swing components. Also with the use of such techniques was achieved implement these APIs 2D and 3D effects to these graphical controls. Note that this application is properly documented with manuals and user programmer for better understanding, both in form and design.